A review of factors limiting physical activity among young children from low-income families - Chang, Seung Ho; Kim, Kijeong (Journal of exercise rehabilitation, 2017)
Children need to participate in structured physical activities to avoid obesity and to engage in sports and games in the future. However, cer-tain groups of our population have little access to enhance levels of physical activity. One such group is children from low-income families who are more likely to have less opportunity for participation in physical activity because of factors such as unsafe streets or limited access to playgrounds. According to the United States Department of Health and Human Services, there is a strong relationship between family income and physical activity with low- income families being the most seden-tary. In order to design effective physical activity interventions for those children, there is a need to identify factors influencing physical activity in these populations, yet, there has been limited research that explores this issue. Therefore, the purpose of this article was to review the litera-ture on factors limiting physical activity among low-income children.